PENGARUH PERSEPSI WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK DAN KEADILAN SISTEM PERPAJAKAN PADA KEPATUHAN PAJAK - Yanti, Meli Dhana; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 20 No 2 (2017), 2017)
Indonesia still has problems regarding taxpayer compliance. Tax compliance is a very complex phenomenon seen from many perspectives. To create compulsory taxpayers requires the willingness of the taxpayer to abide by the rules of taxation and also based on the public perception to the tax climate. Factors influencing tax compliance are taxpayer perception on tax evasion and tax equity system. There is a relationship between the two variables, where if the justice system of taxation that deviates and with addressed through tax cases such as tax evasion will cause the perception of taxpayers to disobey in taxation. The purpose of this study is to determine the effect of taxpayer perceptions about tax evasion and tax system justice regarding tax compliance in Tax Office (KPP) Pratama Badung Selatan. Determination of this study sample using purposive sampling method with respondents in this study amounted to 100 individual taxpayers. The analysis technique is multiple linear regression analysis with SPSS 16.0 program. Based on the analysis result, taxpayer perception about tax evasion and justice of tax system have positive and significant effect on tax compliance. The more well run taxation system that puts a sense of justice for the taxpayer then tax evasion will be reduced so that tax compliance will increase.